Para uma nova caixa de Pandora: esboço de um roteiro heurístico pela sociologia da música - Guerra, Paula (2015)
Although music is present in the works of pioneering authors of sociology (Max Weber and Georg Simmel), it is not possible to speak about a properly consistent field of music within sociological studies, despite the work of some researchers (Simon Frith, Andy Bennett, Antoine Hennion, Tia De Nora, among others), driven in large part by the cultural turn taking place in sociology in the mid-1970s. In view of this panorama, this article aims to contribute to the discussions on the state of the art of the sociology of music from the following questions: a) the necessary balance between the aesthetic approach of music and its due social contextualization; b) the important role of popular music - especially pop-rock - in shaping the identities / practices of specific generational, symbolic and cultural segments; c) the increase - with special emphasis on the Portuguese case - of a cultural sociology that has music as a key theme of its concerns; d) the specific contributions of sociology to the analysis of musical genres - with special emphasis on the case of alternative rock.